Efficacy of Febuxostat with Allopurinol in Chronic Kidney Disease Patients: A Comparative Study - Muhammad Ahmad, Ijaz Nabi, Salman Mehmood, Nouman Hameed Sheikh, Rana Zahid Hafeez, Rashid Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Efficacy of febuxostat with allopurinol in patients of chronic kidney disease Methods: 80 subjects with chronic kidney disease, 20 to 70 years of age with both gender were included. Patients of acute kidney injuries (AKI), acute nephritis, or rapidly progressive glomerulonephritis, liver dysfunction and alcohol abuse were excluded. Group A received febuxostat 40 mg/day for 3 months. Group B patients received allopurinol 100 mg/day for 3 months. Blood samples were sent to the laboratory for serum uric acid level. Results: The mean ± SD age of women in group A and B was 41.8 ± 12.8 and 41.2 ± 10.8 years respectively. Out of 80 cases, 53 (66.3%) were between 20 to 40 years of age. In this study, 55 cases (68.8%) were males and 25 (31.3%) were females. M:F ratio was 2.2:1. This study showed that febuxostat is more effective in reducing uric acid as compared to allopurinol i.e. 72.5% and 45% respectively with p-value of 0.012. Conclusion: Febuxostat is more effective in reducing uric acid as compared to allopurinol in chronic kidney disease cases.